TIKTOK AS A TOOL FOR ENGLISH TEACHER DIGITAL COMPETENCE - Піскурська, Ганна; Попова, Оксана; Скирда, Алла (The Modern Higher Education Review, 2025)
This paper explores the way English language teachers use TikTok as a platform for developing digital competence and creating educational content. The study aims to characterise the pedagogical purposes, content formats, and levels of digital competence demonstrated in teacher-generated TikTok videos. A descriptive qualitative design was employed to analyze 111 videos published under English-teaching-related hashtags. Using an observation checklist based on the European Framework for the Digital Competence of Educators (DigCompEdu), the videos were categorised according to their instructional purpose, format, and technological sophistication. The findings indicate that reflective and personal content predominates, revealing teachers’ tendency to use TikTok for professional self-expression and informal learning rather than structured instruction. Vlogs were identified as the dominant format, reflecting teachers’ preference for authentic, narrative-style communication that humanizes the teaching profession. Most creators demonstrate an intermediate level of digital competence, confidently using the platform’s basic features but rarely applying advanced editing or AI design strategies. The study concludes that TikTok contributes to the enhancement of teachers’ digital, communicative, and creative competences, however, its interactive and assessment-oriented potential remains underused. The paper highlights the need for targeted professional development to support educators in transforming social media into a strategic environment for innovative teaching and digital literacy growth.